Bioinformatics Study of Hibiscus Flower (Hibiscus rosa-sinensis) Against Diabetes - Febriyani, Siska; Mustika, Melani; Febriyanti, Rada; Azhike, Vioni Yuliof de (Journal of Catalyst and Bioinformatics (Catalytic), 2022)
People often experience diabetes problems. Adequate and intensive treatment is expensive. Hibiscus flower (Hibiscus rosa-sinensis L) has potential as an alternative medicine for diabetes mellitus. The active ascorbic-acid compound with the name IUPAC (2R) -2 - [(1S) -1,2-dihydroxyethyl] -3,4-dihydroxy-2H-furan-5-one found in this part of the flower plays a role in treating disease diabetes mellitus. The purpose of this study was to determine the efficacy of hibiscus flowers for the health of the body. Hibiscus flowers are very useful including helping the healing process of diabetes mellitus because this plant contains ascorbic acid or vitamin C which is believed to be able to treat diabetes mellitus. The research method used is library research where data sources are obtained from primary data sources and secondary data sources. This method is a combination of descriptive, comparative, qualitative and quantitative methods.